A single bout of cycling exercise effects on short term memory - Mohbin, Najihah (2018)
Exercise plays a role in enhancing neurogenesis and brain plasticity. Actively involved in a musculoskeletal and cardiovascular activities at moderate intensity influences brain systems that involve in working memory processes. The aim of this study was to investigate the effects of single bout exercise on short term memory. Methods: A total of 16 female university students with mean age of 23.63 ± 1.46 year old were involved in this study. Participants completed free recall test twice which was once pre- and once post-exercise. Exercise session involved a single bout cycling ergometer at 50 watts while maintaining 60 rpm for 30 minutes and two five minutes periods of warm up and cools down at 20 watts. Results: Percentage of words recalled in free recall test post-exercise did not improved compared to pre-exercise. Percentage of recency words recalled post-exercise (51.25 ± 21.87 %) is higher than pre-exercise (48.75 ± 21.87 %) but no significant difference compared to pre-exercise (p=0.751). The percentage of words recalled post-exercise was correlated with heart rate during exercise (r = -0.59, p=0.015). Participants with higher heart rate during exercise had a lower percentage of words recalled at post compared to pre-exercise. Conclusion: A single bout of cycling exercise did not improve short term memory.